The Comparison of the Effect of Plyometric Depth Jump Exercise and Plyometric Box Jump Exercise on the Improvement of Leg Muscle Strength in Diamond Volleyball Athletes of Medan in 2024 - Simson Sinuhaji; Ananda Salsabila (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Physical, mental, and social well-being is defined as a condition that enables individuals to live a productive life. Exercise helps maintain health and enhances both physical and mental fitness. Volleyball, a physical sport that is increasingly popular in Indonesia, requires several physical attributes such as speed, explosive power, and agility to perform well. Sports are an effective way to maintain optimal physical and mental condition, while also fostering character, discipline, and sportsmanship. Volleyball continues to grow in popularity in Indonesia and is played at various levels of competition. The physical performance of volleyball athletes is crucial to achieving high performance, thus requiring specific training methods to improve physical attributes such as speed, power, and agility. Plyometric depth jump and plyometric box jump are two common forms of plyometric training used to improve lower limb muscle strength. However, despite the widespread application of plyometric training, the comparative effectiveness of various training methods in enhancing lower limb strength still requires further investigation. The aim of this study is to analyze and compare the effects of plyometric depth jump exercise and plyometric box jump exercise on increasing leg muscle strength in volleyball athletes. Methods: This study uses an experimental approach with a two-group pre-test and post-test design. A total of 12 selected volleyball athletes participated in a training program using either plyometric depth jump exercise or plyometric box jump exercise over a specific period. Leg muscle strength was measured using a leg dynamometer before and after the intervention. Data were analyzed using an independent t-test to determine the difference in the effect of plyometric depth jump exercise and plyometric box jump exercise on improving leg muscle strength of Diamond Medan volleyball athletes in 2024. Results and Discussion: The results of data analysis showed a significant increase in leg muscle strength after the intervention in both the plyometric depth jump exercise group and the plyometric box jump exercise group, with the simple paired t-test showing a p-value = 0.000 (<0.05). However, based on the independent t-test, a p-value of 0.326 (>0.05) was obtained, indicating that there was no significant difference between the two training methods in improving leg muscle strength. Conclusion: Both plyometric depth jump exercise and plyometric box jump exercise have an effect on increasing leg muscle strength in volleyball athletes. However, no significant difference was found between the two interventions in their effect on improving leg muscle strength